The study of applying the six methods in forming chinese characters (六书) for the teaching of chinese as the third Language at UiTM Terengganu / Wong Hoong Cheong, Goh Ying Soon & Yap Soh Leay - Wong, Hoong Cheong; Goh, Ying Soon; Yap, Soh Leay
Learning Chinese characters is essential in learning Chinese language, especially in learning Chinese as a foreign language or the third language. However, it is often observed that Chinese characters learning is deemed to be the weakness for non-native Chinese learners. Six Methods of forming Chinese characters (六书) is the most basic and unsophisticated method to study Chinese characters since ancient times. After analyzing the structures of Chinese characters and explaining the rationales of the structures of these Chinese characters, these non-native students were able to learn the Chinese culture which were carried in these Chinese characters. It will certainly enhance the joy of learning in the learning process. By applying the Six Methods of forming Chinese characters ( 六 书) in interpreting and elaborating the explanation on these Chinese characters, the non-native students can have a better and deeper understanding of Chinese cultures. These non-Chinese students who were from different nationalities and races can apprehend and appreciate Chinese culture more. This also can contribute to the building of national unity in Malaysia.